The Importance of Free Zones in Terms of Foreign Trade and Employment in Turkey During the COVID-19 Period - Avcı, Zafer; Kovacı, Süreyya; Şen, Süleyman (Fırat University, 2022)
Free zones; it has positive effects in terms of foreign direct investment, technology transfer, employment creation, and its contribution to foreign trade volume. However, because of the companies in free zones have a privileged place compared to companies outside the free zone, there are also opinions that free zones cause unfair competition. In this study, it is aimed to examine the importance of free zones operating in Turkey in terms of foreign trade and employment during the COVID-19 period. For this purpose, first of all, the foreign trade share of the eighteen free zones in Turkey and the employment they provide were evaluated comparatively. During the pandemic period, the contribution of free zones to foreign trade did not decrease; on the contrary, it increased. The foreign trade volume of the free zones has increased by 12.22% in 2020 compared to the pre-epidemic period. Simultaneously, the effect of free zones on employment has increased by 7.19% compared to pre-epidemic period. As a result of the econometric analyzes, it was confirmed that the increase in the foreign trade volume of free zones positively affected the employment of free zones despite the negative effects of the epidemic.

Serbest bölgeler; doğrudan yabancı yatırım, teknoloji transferi, istihdam oluşturma ve dış ticaret hacmine katkısı bakımından olumlu etkilere sahiptir. Ancak, serbest bölgelerde yer alan firmaların, serbest bölge dışındaki firmalara kıyasla ayrıcalıklı bir yere sahip olması nedeniyle serbest bölgelerin haksız rekabete yol açtığına yönelik görüşler de bulunmaktadır. Bu çalışmada, COVID-19 döneminde Türkiye’de faaliyet göstermekte olan serbest bölgelerin dış ticaret ve istihdam açısından önemini incelemek amaçlanmıştır. Bu amaç doğrultusunda, öncelikle Türkiye’de yer alan on sekiz adet serbest bölgenin dış ticaret içerisindeki payı ve sağladığı istihdam karşılaştırmalı olarak değerlendirilmiştir. Karşılaştırmalı analizlerden elde edilen sonuçlara göre, salgın döneminde serbest bölgelerin dış ticarete katkısı azalmamış, tam tersine artmıştır. Serbest bölgelerin salgın öncesine göre dış ticaret hacminde, % 12,22 artış meydana gelmiştir. Aynı zamanda serbest bölgelerin salgın öncesine göre 2020 yılında istihdama etkisi de % 7,19 artmıştır. Yapılan ekonometrik analizler sonucunda, salgının olumsuz etkilerine rağmen, serbest bölgelerin dış ticaret hacmindeki artışın serbest bölgelerin istihdamını pozitif etkilediği teyit edilmiştir.
TÜRKİYE’DE COVID-19 DÖNEMİNDE SERBEST BÖLGELERİN DIŞ TİCARET VE İSTİHDAM AÇISINDAN ÖNEMİ